Effect of The Calcination on The Properties of Hydroxyapatite from Patin Fish Bone for Biomedical Use - Arisha Rifhan binti Azman,; Abdullah, Hasan Zuhudi (Research Progress in Mechanical and Manufacturing Engineering, 2023)
Most of the inorganic components in human bones are calcium phosphate, which occurs naturally. Hydroxyapatite (HAp) has been used extensively to rebuild bone. is the chemical formula for HAp, and the Ca/P ratio is 1.67. This study is to extract HAp powder from patin fish bone and investigate the effect of calcination on the properties of HAp. The extraction process involved cleaning, boiling, drying, grinding, and milling process to obtain micron size powder of the patin fish bone. The characteristics of produced HAp powder were characterized with Scanning Electron Microscope (SEM), Energy Dispersive X-ray Spectroscopy (EDS), X-ray Diffraction (XRD), and Fourier Transform Infrared Spectroscopy (FTIR). EDS and XRD testing confirmed that calcium and phosphorus elements existed in the HAp samples. The best hydroxyapatite is from patin fish bone sample with a calcination temperature 900 with Ca/p ratio of 1.64.